Business Strategic and Implementation of Digital Startup of Usable Goods Commerce in Samarinda City - Aksenta, Almasari; Nawawi, Muhammad; Audhis, Allayza (Institute of Computer Science (IOCS), 2024)
Environmental pollution is a major problem in sustainable development today. Utilizing unused goods is a solution that can be offered to people in need without having to throw them away as a potential for reducing non-organic waste. Useable goods that are sold provide economic value for the buyer and additional income for the seller. This business of buying and selling usable goods is assisted by information technology, namely by creating digital applications to assist in marketing. Businesses using this application also support the creative economy in Indonesia and are implementing Green Technology, namely this digital technology supports all environmentally friendly practices. This business concept is applied in Samarinda City, which is a city that is currently making a lot of developments in terms of digital startups, especially preparing for the rapid growth of the Indonesia National Capital. This research aims to analyze business strategies and implement digital startups in the business of buying and selling usable goods in Samarinda City. The research method was carried out in the stages of observation, interviews, data collection. Then, carry out a business planning strategy using the Business Canvas Model and create a digital startup in the e-commerce model